2018
DOI: 10.1038/s41598-018-33561-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of reference genes for RT-qPCR data normalization in Gammarus fossarum (Crustacea Amphipoda)

Abstract: Gene expression profiling via RT-qPCR is a robust technique increasingly used in ecotoxicology. Determination and validation of optimal reference genes is a requirement for initiating RT-qPCR experiments. To our best knowledge, this study is the first attempt of identifying a set of reference genes for the freshwater crustacean Gammarus fossarum. Six candidate genes (Actin, TUB, UB, SDH, Clathrin and GAPDH) were tested in order to determine the most stable ones in different stress conditions and to increase th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…Reference gene validation has been performed in many other aquatic invertebrates, such as cladocera Daphnia magna 13 , amphipod Gammarus fossarum 14 , and bivalves Pecten maximus L. 37 and Ruditapes philippinarum 38 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reference gene validation has been performed in many other aquatic invertebrates, such as cladocera Daphnia magna 13 , amphipod Gammarus fossarum 14 , and bivalves Pecten maximus L. 37 and Ruditapes philippinarum 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Commonly used reference genes contain the 18S rRNA, β-actin, and GAPDH genes 10,11,12 in crustaceans (mainly large crustaceans). Few studies have validated reference genes in small crustaceans 13,14 . It has been suggested that the expression of reference genes can be modulated by different environmental stresses 15 , indicating that some housekeeping genes may be involved in pathways other than cellular homeostasis 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Since all the housekeeping genes tested (actin-C, eif2, rpl13, gapdh, clathrin) presented the same pattern for all SIM tested concentrations ( Figure 3), it is plausible to hypothesize that G. locusta, at the highest SIM concentration (8 µg.L -1 ), was experiencing an increase in the overall metabolism. A recent study calculated the stability coefficient of several candidate reference genes in Gammarus fossarum using five different algorithms and showed that clathrin and gapdh were the two most stable genes in this species [67]. Given that the reference genes must show a stable transcriptional pattern across treatments [68], the qRT-PCR data was normalized here with clathrin and gaphd, the genes with the most similar transcription levels to the genes of interest.…”
Section: Gene Transcription Of Epigenetic Regulatorsmentioning
confidence: 99%
“…Nonetheless, using RT-qPCR to investigate gene expression levels requires stably expressed reference genes for data normalization, and the expression stability of reference genes directly affects the accuracy of relative quantitative analyses [7,[9][10][11][12]. In theory, reference genes should have stable expression patterns in different samples and under different experimental conditions, yet no reference gene has satis ed these conditions simultaneously [8,11,[13][14][15][16]. To our knowledge, a candidate reference gene may exhibit distinct expression patterns in different tissues within a species, and it may also exhibit various expression patterns under different conditions even in the same tissue [15,17,18].…”
Section: Introductionmentioning
confidence: 99%